Metastatic breast cancer presenting as acute liver injury: diagnostic dilemma in the setting of suspected hemochromatosis. Issue 3 (6th May 2020) - Chandradevan, Raguraj; Takeda, Hironobu; Hayes, Benjamin; Faulkner, Kalli; Darrow, Matthew
Abstract: A 70-year-old female with a history of lobular carcinoma of the breast, status post-mastectomy followed by adjuvant radio-chemotherapy in remission for 4 years was admitted with the features of acute liver failure (ALF). Iron studies revealed a hemochromatosis picture and the CT and MRI scans of the abdomen suggested cirrhosis. An extensive workup failed to identify an etiology. A trans-jugular liver biopsy was obtained and revealed poorly differentiated carcinoma consistent with the metastasis of breast primary. The patient's condition deteriorated and died within a week following the onset of acute hepatic failure. DNA testing revealed that the patient was heterozygous for H63D mutation. In cases of ALF with the suspicion of malignancy, liver biopsy should be obtained to evaluate an infiltrative hepatic disease.